Antifungal compounds from Streptomyces associated with attine ants also inhibit Leishmania donovani. - Humberto E Ortega; Leonardo L G Ferreira; Weilan G P Melo; Ana Ligia L Oliveira; René F Ramos Alvarenga; Norberto P Lopes; Tim S Bugni; Adriano D Andricopulo; Mônica T Pupo (Public Library of Science (PLoS), 2019)
Bacterial strains isolated from attine ants showed activity against the insect specialized fungal pathogen Escovopsis and also against the human protozoan parasite Leishmania donovani. The bioassay guided fractionation of extracts from cultures of Streptomyces sp. ICBG292, isolated from the exoskeleton of Cyphomyrmex workers, led to the isolation of Mer-A2026B (1), piericidin-A1 (2) and nigericin (3). Nigericin (3) presented high activity against intracellular amastigotes of L. donovani (IC50 0.129 ± 0.008 μM). Streptomyces puniceus ICBG378, isolated from workers of Acromyrmex rugosus rugosus, produced dinactin (4) with potent anti-L. donovani activity against intracellular amastigotes (IC50 0.018 ± 0.003 μM). Compounds 3 and 4 showed good selectivity indexes, 88.91 and 656.11 respectively, and were more active than positive control, miltefosine. Compounds 1-4 were also active against some Escovopsis strains. Compounds 1 and 2 were also produced by Streptomyces sp. ICBG233, isolated from workers of Atta sexdens, and detected in ants' extracts by mass spectrometry, suggesting they are produced in the natural environment as defensive compounds involved in the symbiotic interaction.